2013
DOI: 10.1080/17533015.2013.817447
|View full text |Cite
|
Sign up to set email alerts
|

Visible Voices: Expressive arts with isolated seniors using trained volunteers

Abstract: This practice-based paper describes an innovative program from Ontario, Canada that explored the potential for volunteer-facilitated expressive arts to contribute to the well-being of socially isolated rural seniors. Inspired by Arts on Prescription initiatives in the UK and coordinated by a Registered Expressive Arts Consultant/Educator, the program involved eight older volunteers and eight older participants engaged in a 10-week series of one-on-one intermodal art-making activities in the participants’ homes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…Permission to use their names connected to their artwork for use in public installations was acquired with informed consent; however, only pseudonyms are used in the reporting of the research results and in related publications and presentations. The volunteer training, matching of volunteers to participants and full description and evaluation of the program, a 10-week series of one-on-one intermodal art-making in the participants’ homes and institutional settings is discussed in a companion article (Wilkinson et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Permission to use their names connected to their artwork for use in public installations was acquired with informed consent; however, only pseudonyms are used in the reporting of the research results and in related publications and presentations. The volunteer training, matching of volunteers to participants and full description and evaluation of the program, a 10-week series of one-on-one intermodal art-making in the participants’ homes and institutional settings is discussed in a companion article (Wilkinson et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In order to extend the impact of art-making to support expression of the self in relation to others, expressive arts amplify personal expression by using different modalities whereby the focus is as much on the creative process as it is on the final outcome or product (Wilkinson et al, 2013). In addition, arts-based participatory inquiry methods are most empowering for participants when designed to address relevant research questions (Fraser & Al Saya, 2011; Leavy, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fraser, Bungay, and Munn-Giddings (2014) showed that participatory visual arts (i.e., clay modelling and painting) resulted in increased levels of engagement for older adults in residential care. Wilkinson et al (2013) found an expressive arts program gave isolated seniors in rural communities and institutional settings an opportunity to “learn about the aging process, open doors to new perceptions and increased confidence” (p. 234).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet there is increasing recognition that professionally taught arts programs can offer significant benefits for reducing social isolation, increasing self-esteem, and providing participants with a sense of empowerment (Camic, 2008; Roos & Malan, 2012). In a study of a professionally taught arts program in a long-term care facility, Wilkinson, MacLeod, Skinner, and Reid (2013) found an improvement in participant well-being, creative expression, and sense of meaning. This finding emerged from an analysis of field notes, weekly logs kept by program volunteers, transcripts of volunteer debriefing meetings, and program evaluation questionnaires which were completed by both volunteers and participants.…”
Section: Introductionmentioning
confidence: 99%